La medicina del lavoro di fronte alle nuove sfide socio-sanitarie: l’esempio delle alcol dipendenze / Occupational Medicine faces new health challenges: the example of alcohol dependence - Ferrario, M.M.; Apostoli, P.; Bertazzi, et al., P.A. (La Medicina del Lavoro, 2007)
Occupational Medicine faces new health challenges: the example of alcohol dependenceThe regulations for application of the legislation on control of alcohol consumption at the work place, which were published in the Gazzetta Ufficiale No. 75, March 30, 2006, set the occupational physician a more challenging task, in addition to regular activities related to the prevention of the usual work-related risk factors. The aim of the legislation, which was derived from and inspired by the European Alcohol Action Plan 2000-2005, drawn up by the European Office of the WHO, is to prevent alcohol abuse and its consequences, i.e. accidents and injuries to third parties, and to permit subjects with alcohol dependence to go on working. In this context, occupational physicians are asked to contribute to the early identification of subjects prone to alcohol abuse and assess whether alcohol-dependent subjects can return to work in conditions of safety for themselves and for other workers. Various problems arise for the achievement of these aims in practice, and concern confidentiality, ethical aspects, i.e. use of alcohol screening at hiring, integration of such tests with those used for monitoring conventional occupational exposures, interactions with exposures to other chemical products, just to mention the major issues. Due to these difficulties in the application of the new regulations, field trials become all the more important, since they offer the possibility of assessing efficacy and efficiency of the different approaches.